MOODLE SYSTEM IN TEACHING “INFORMATION TECHNOLOGY AND PROCESS MODELING” FOR ISLAMIC STUDIES STUDENTS - Turdali Jumayev; Mavlyuda Xodjayeva; Alimjon Dadamuxamedov (International Engineering Journal For Research & Development, 2020)
This article is devoted to the use of the Moodle system in education, in particular in the subject “Information technologies and mathematical modeling of processes". students of the direction of Islamic studies. At the end of the XX century, humanity faced a number of problems that are directly related to serious changes in the field of information telecommunications, especially with the accelerated development of information technologies. New means of communication began to penetrate into various spheres of education and production. The development of the global computer network Internet has led to the opening of new directions for improving the world education system. The development of the global computer network Internet has led to the opening of new directions for improving the world education system. The development of the global computer network Internet has led to the opening of new directions for improving the world education system. In particular, a sharp change in the technical support of educational institutions and the wide opening of secular information resources have created the need to use new forms and methods of teaching. In distance education, students and teachers continuously communicate with each other using specially created training courses, forms of control, electronic communications, and other Internet technologies. Distance learning based on the use of Internet technologies provides access to a worldwide educational information network. The use of distance learning technologies in the organization of the educational process and the rapid introduction of new information into science will ensure high efficiency. This will also create opportunities for quickly obtaining additional information on the subject area of virtual research[3]. This means that the study of methods of implementing remote technologies in the educational process and methods of their effective use, the creation of remote educational courses, belongs to the category of topical scientific and technical issues. In accordance with the above, the use of the Moodle system in teaching the discipline "Information technologies and process modeling" to students of the Islamic direction is one of the current topics in the direction of using distance learning technologies in the educational process. They mentioned the capabilities of the Moodle system, the advantages of course elements, and effective methods of teaching natural Sciences. In particular, in the case of using this system, it was reported that the distance learning teacher will create a database that includes questions for repeated use in various tests on the web interface, the use of electronic learning resources in the educational process.